Breast Cancer Therapeutics and Biomarkers: Past, Present, and Future Approaches. (March 2021) - Schick, Jason; Ritchie, Raquel P; Restini, Carolina
Breast cancer (BC) is the leading cause of cancer death in women and the second-most common cancer. An estimated 281 550 new cases of invasive BC will be diagnosed in women in the United States, and about 43 600 will die during 2021. Continual research has shed light on all disease areas, including tumor classification and biomarkers for diagnosis/prognosis. As research investigations evolve, new classes of drugs are emerging with potential benefits in BC treatment that are covered in this manuscript. The initial sections present updated classification and terminology used for diagnosis and prognosis, which leads to the following topics, discussing the past and present treatments available for BC. Our review will generate interest in exploring the complexity of the cell cycle and its association with cancer biology as part of the plethora of target factors toward developing newer drugs and effective therapeutic management of BC.